Studencka „rewolucja na granicie” w kontekście przemian społeczno-politycznych w Ukraińskiej Socjalistycznej Republice Radzieckiej - Hurska-Kowalczyk, Liana (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The paper analyses the student campaign of civil disobedience organised in October 1990 and later named ‘the granite revolution.’ During the ‘granite revolution,’ students demonstrated their socio-political awareness, taking decisions of key importance at that time. The author of the paper also analyses the outcomes of the ‘granite revolution’ and its significance for further socio-political developments in Ukraine.